Correction: Highly modulated supported triazolium-based ionic liquids: direct control of the electronic environment on Cu nanoparticles. Issue 6 (12th May 2020) - Valdebenito, Cristián; Pinto, Jose; Nazarkovsky, Michael; Chacón, Gustavo; Martínez-Ferraté, Oriol; Wrighton-Araneda, Kerry; Cortés-Arriagada, Diego; Camarada, María Belén; Alves Fernandes, Jesum; Abarca, Gabriel
Abstract : Correction for 'Highly modulated supported triazolium-based ionic liquids: direct control of the electronic environment on Cu nanoparticles' by Cristián Valdebenito et al., Nanoscale Adv., 2020, 2, 1325–1332. DOI: ; 10.1039/d0na00055h .